Face-to-face in Shakespearean drama : ethics, performance, philosophy - Smith, Matthew James; Lupton, Julia Reinhard, 1963- (Edinburgh University Press, 2019)
This book celebrates the theatrical excitement and philosophical meanings of human interaction in Shakespeare.